2018
DOI: 10.2478/ttj-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Side Friction on Urban Arterials

Abstract: The influence of the side friction activities on the speed has been analyzed in the present study by conducting series of traffic field surveys. Pedestrian movements, parked vehicles and entry-exit of vehicles from surroundings, and wrong way movements are observed from videos and analyzed to estimate weighing factors. To examine the combined effects of all the activities the weighing factors are used to determine total value of side friction on the road. The study suggests model to estimate average speed of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
(4 reference statements)
1
11
0
1
Order By: Relevance
“…However, the authors considered only 90% confidence level (CI) to infer about the statistical significance of coefficients through p values, and it was found that many side friction variables become insignificant when the usual 95% CI is considered. In Gulivindala and Mehar [9] study, the R 2 values were not at all reported and some of the variables like frequency of pedestrians, parked vehicles and wrong movement had p values more than 0.05, but still they have been considered. The review of existing studies leads to the following gaps as explained below.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the authors considered only 90% confidence level (CI) to infer about the statistical significance of coefficients through p values, and it was found that many side friction variables become insignificant when the usual 95% CI is considered. In Gulivindala and Mehar [9] study, the R 2 values were not at all reported and some of the variables like frequency of pedestrians, parked vehicles and wrong movement had p values more than 0.05, but still they have been considered. The review of existing studies leads to the following gaps as explained below.…”
Section: Introductionmentioning
confidence: 87%
“…Many studies have reported the impact of side friction on speed-flow characteristics since 1980s [2][3][4][5], and they can be broadly divided into two groups. One is relating friction parameters with the speed observed at stretches where side friction elements are present [1,3,[6][7][8][9]. Regression models were developed to quantify the relationship, and with the developed models it would be easy to predict the speed for varying levels of side friction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance a vehicle maintains with adjacent vehicles is called the lateral distance headway. A small lateral distance headway tends to reduce traffic flow and vice versa [3]. Thus, traffic models should consider both the lateral and forward distance headways to adequately characterize traffic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in India developed speed prediction models taking into account roadside friction factors. For instance, (Gulivindala and Mehar, 2018) incorporated into the model events/hr to represent the effects of roadside friction, while Salini et al (2014) considered the effects of the number of cars, two-wheelers, and three-wheelers as well as dwell times, number of pedestrians per minute, number of parking maneuvers, number of vehicles parked on sides of the carriageway, and influence of time of parking and un-parking vehicles. In (Dar es Salam and Chiguma, 2007) developed a speed prediction model that considered roadside friction factors during actual conditions.…”
Section: Introductionmentioning
confidence: 99%